(untitled) (Research, Society and Development, 2021)
Most of the industrially produced rubber is used in the manufacture of tires, which corresponds to 70% of world production. Another part of the production is used in the manufacture of automotive parts, products for the medical, packaging, civil construction and other sectors. In the automotive industry, the manufacture of parts used in the driving system, components for sealing in the car body, control and sealing of brake fluids, cooling, lubrication, as well as in the absorption from impacts and driving force stands out. In most of the elastomeric components of seals, we highlight the rings, which are produced with specific materials and manufacturing processes that vary according to the type of seal in which it should act. In this context, the present work was developed in the form of a case study in a company in the automotive sector, which produces elastomeric seals. Data were collected related to the composition of the seals, the number of parts produced and imported by the company from its units abroad, data related to losses in the processing of raw materials and energy consumption. Thus, the most prominent products were sealing rings (orings), with a greater proportion in the quantity of parts produced, as well as responsible for the greater amount of waste (scraps) generated.